ASAS, PRINSIP, DAN PERMASALAHAN ETIKA DALAM BISNIS - Sudiah Hestianah; Khuriyatul Mutrofin; Fatimah Azzahra (Dar El-Falah, 2023)
The basic principles in doing business are: like and don't harm other people.Meanwhile, business principles in practice include: the principle of autonomyin business ethics, honesty in business, fairness in business, honesty inbusiness. There are three factors that generally cause business ethics problemsin companies, namely: Pursuit of profit and personal interests, competitivepressure on company profits, and conflict between company and individualvalues. Business ethics are rules that must be fulfilled by all business people.Business ethics has a wider reach compared to written rules. By implementingbusiness ethics, the sustainability of a business will be guaranteed because anethical business has a good image in front of many people, in this casecustomers are the priority.